Persepsi Pekebun Swadaya Terhadap Penerapan Indonesian Sustainabel Palm Oil (ISPO) di Kabupaten Muaro Jambi - Muchlis, Fuad; Farida, Aulia; Kurniasih, Siti (AGRINUS : Jurnal Agro Marin Nusantara, 2024)
Indonesia Sustainable Palm Oil (ISPO) exists as a response to the negative impact on the environment caused by the expansion of palm oil production in Indonesia. ISPO creates standards to accelerate the adoption of better practices in sustainable palm oil plantations. However, the level of adoption by independent smallholders of ISPO recommended practices is still low. The research aims to describe the perceptions of independent smallholders regarding the implementation of ISPO.  The research was conducted purposively in Sungai Bahar District, Muaro Jambi Regency and analyzed descriptive qualitative. The research results show that the majority of independent smallholders have low knowledge of ISPO implementation; Even though independent smallholders' knowledge of ISPO is relatively low, their perception is positive towards ISPO principles and criteria, both in the aspects of legality and plantation management, smallholder organization and management of independent smallholders' plantations, environmental management and monitoring, and sustainable business improvement. This positive perception is a good indication for the implementation of ISPO in independent oil palm plantations in the future. Keywords: ISPO, palm oil, smalhoders